Design of wind nozzle for nozzle augmented wind turbine - Mohammed Aldhufairi; Muda, Mohd Khairul Hafiz; Mustapha, Faizal; Ahmad, Kamarul Arifin; Yidris, Noorfaizal (Semarak Ilmu Publishing, 2022)
In some countries, wind turbines are designed to operate at relatively high speeds to be appropriately efficient, limiting the use of wind turbines in urban areas with low wind speeds. Thus, innovation is needed to enhance the possibility of wind energy use within the range of low speeds. In order to increase the electrical power of the wind turbines, the velocity of the wind blowing on the wind turbine, is the most important factor that has to increase. In this paper it has been recommended that contraction nozzles could be applied between Wind Turbines and wind-way to provide the wind through themselves with more velocity. The main objective of this research is to optimize the nozzle design for vertical axis wind turbine (VAWT). Specifically, this study investigates the effect of wind velocity on different shapes of nozzle to develop the suitable nozzle for the wind turbine. For that purpose, the ideologies of contraction nozzle have been studied. Different nozzle design concepts were developed and the wind speed for each design is simulated.